Effects of bulevirtide on atherosclerosis in an ApoE-deficient mouse model - Jonas Rusnak; Victoria Delcheva; Dirk Theile; Antje Blank; Norbert Frey; Michael R. Preusch (PLoS ONE, 2026)
Objective Bile acids are known to have a positive impact on atherosclerosis. The study investigates the impact of sodium taurocholate co-transporting polypeptide (NTCP) inhibition with bulevirtide, organic anion transporting polypeptide (OATP) inhibition with rifampicin, and their combination on bile acid levels and atherosclerosis in apolipoprotein E–deficient (ApoE⁻/⁻) mice. Methods Fifty-six female ApoE⁻/⁻ mice on a Western type diet were treated daily for four weeks with bulevirtide (5 mg/kg), rifampicin (20 mg/kg), a combination of both, or vehicle. Plasma bile acids and lipids were measured at sacrifice. Atherosclerotic lesion size was quantified in the aortic sinus, and macrophage content was analyzed by Mac-2 immunohistochemistry. Results Plasma cholesterol, low-density lipoprotein (LDL), high-density lipoprotein (HDL), and triglyceride levels remained unchanged across all groups, being accompanied with no changes of atherosclerotic lesion size (p = 0.896). However, treatment with bulevirtide (p = 0.017), rifampicin (p = 0.003), but mostly their combination (p < 0.001) significantly increased plasma bile acid concentrations and altered the macrophage-to-lesion area ratio, at least for the combination therapy group (p = 0.020). The combined treatment exhibited the highest bile acid levels, indicating additive effects of dual transporter inhibition. Conclusions While lesion sizes remained unaffected, the combined NTCP and OATP inhibition significantly enhanced bile acid levels and reduced macrophage content in early atherosclerotic lesions of ApoE⁻/⁻ mice. These results highlight the association of bile acid with the modulation of plaque composition as a potential therapeutic mode of action.